Піоглітазон у лікуванні хворих на цукровий діабет 2-го типу - Кіхтяк, О. П. (Clinical Endocrinology and Endocrine Surgery, 2012)
Decreasing of insulin level without any changes of C-peptide was observed during treatment with pioglitazone in patients with type 2 diabetes mellitus. This may suggest enhancing of peripheral insulin binding to its receptors. Treatment with pyoglitazone promotes increase in insulin resistance by the following laboratory criteria: ÍbÀ1ñ, fasting insulin and glucose, adiponectin. Elevation of adiponectin level following treatment with pyoglitazone may be the evidence of clinically important affect toward insulin resistance of adipose tissue, as well as on insulin resistance in muscles and vessels.